2023
DOI: 10.1039/d2dt03791b
|View full text |Cite
|
Sign up to set email alerts
|

Novel 1,2,3-triazolyl phosphine with a pyridyl functionality: synthesis, coinage metal complexes, photophysical studies and Cu(i) catalyzed C–O coupling of phenols with aryl bromides

Abstract: This manuscript describes the synthesis and coinage metal complexes of pyridine appended 1,2,3-triazolyl-phosphine [2-{(C6H4N)(C2(PPh2)N3C6H5)}] (1), photophysical studies and catalytic application. The reactions of 1 with copper salts afforded dimeric complexes...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…10 The P1–Cu1 and Cu1–Cl1 bond lengths in complex 2 are 2.2437(8) and 2.3490(7) Å, respectively, which are in accordance with the recently isolated PONNOP-based dimeric copper( i ) complexes. 11 The interatomic Cu⋯Cu distance in complex 2 was found to be 3.1750 (9) Å, which is longer than the previously reported bidentate phosphinite dinuclear copper chloride by Tsuboyama and Balakrishna et al 12 and in accordance with the copper chloride complex of DuPhos reported by Patterson and co-workers 13 but shorter than those reported for [ o -{PPh 2 C 3 H 2 N 2 (Me)}C 5 H 4 PPh 2 (Cu(μ 2 -I))] 2 (OTf) 2 (Cu⋯Cu = 3.345 Å) and [ o -{PPh 2 C 3 H 2 N 2 }C 5 H 4 PPh 2 (Cu(μ 2 -I))] 2 (Cu⋯Cu = 3.499 Å). 14 When we treated 1 with two equivalents of copper bromide and iodide in dichloromethane, complexes 3 and 4 were produced, respectively (Scheme 1).…”
Section: Resultsmentioning
confidence: 55%
“…10 The P1–Cu1 and Cu1–Cl1 bond lengths in complex 2 are 2.2437(8) and 2.3490(7) Å, respectively, which are in accordance with the recently isolated PONNOP-based dimeric copper( i ) complexes. 11 The interatomic Cu⋯Cu distance in complex 2 was found to be 3.1750 (9) Å, which is longer than the previously reported bidentate phosphinite dinuclear copper chloride by Tsuboyama and Balakrishna et al 12 and in accordance with the copper chloride complex of DuPhos reported by Patterson and co-workers 13 but shorter than those reported for [ o -{PPh 2 C 3 H 2 N 2 (Me)}C 5 H 4 PPh 2 (Cu(μ 2 -I))] 2 (OTf) 2 (Cu⋯Cu = 3.345 Å) and [ o -{PPh 2 C 3 H 2 N 2 }C 5 H 4 PPh 2 (Cu(μ 2 -I))] 2 (Cu⋯Cu = 3.499 Å). 14 When we treated 1 with two equivalents of copper bromide and iodide in dichloromethane, complexes 3 and 4 were produced, respectively (Scheme 1).…”
Section: Resultsmentioning
confidence: 55%
“…24 Recently we reported dimeric copper(I) complexes of the type [{Cu(m 2 -X)} 2 -{2-(C 5 H 4 N)(C 2 (PPh 2 )N 3 C 6 H 5 )} 2 ] (X = Cl, Br, and I), showing solid-state fluorescence due to short non-bonded CuÁ Á ÁCu distances. 11 The UV-Vis absorption spectra for complexes 1-3 Table 1 Selected bond lengths (Å) and bond angles (1) of complexes 1-3 were taken in 1,2-dichloroethane at room temperature and are shown in Fig. 3.…”
Section: Photophysical Studies Of Complexes 1-3mentioning
confidence: 99%
“…Cu( i ) complexes continue to attract research attention due to their interesting photophysical properties 11 and also their significant catalytic potential to effect a variety of cost-effective organic transformations. 12 A highly distorted [Cu(PNP Me ( i Pr))Br] complex reported by Kirchner and co-workers promoted C–C and C–N cross-coupling reactions very efficiently.…”
Section: Introductionmentioning
confidence: 99%